The Role of Small Business Entities in the Development of the Economy of Uzbekistan - Safaraliyevich, Mamatov Bahadir (Miasto Przyszłości, 2024)
This article examines the role and importance of small business and private entrepreneurship in the development of the economy. The features and stages of entrepreneurship development are described. The number of operating small enterprises and microfirms, newly created small enterprises and microfirms, as well as the share of small business in the gross domestic product of the country were studied. Based on the results of the study, problems in the development of small businesses are described, as well as proposals and recommendations aimed at the further development of small business are developed.